Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Restoring a Healthier Nerve Phenotype: Mechanistic Insights into High-Concentration Capsaicin Topical System (HCCTS) for Painful Diabetic Peripheral Neuropathy (PDPN) - David M. Simpson; Samuel Allen; Audrey Carnevale; Jennifer Lohf (Toxicon, 2026)

Comparing the Impact of the High-Concentration Capsaicin Topical System (HCCTS) on Pain and Sleep in Patients With Painful Diabetic Peripheral Neuropathy (PDPN): Findings from the STEP Randomized Trial and the Real-World CASPAR Study - David M. Simpson; Samuel Allen; Audrey Carnevale; Lizandra Marcondes; Mariëlle Eerdekens (Toxicon, 2026)

Long-term biomass removal in grasslands reduces plant and soil phosphorus, increases carbon:phosphorus stoichiometry, but does not lead to microbial phosphorus limitation - Andrea Simpson; David Whitehead; Leo M. Condron; Kate H. Orwin; Keith C. Cameron; Niklas J. Lehto (Agriculture, Ecosystems & Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Combining analysis of individual and wastewater whole genome sequencing improves SARS-CoV-2 surveillance - Evan P. Troendle; Andrew J. Lee; Marina I. Reyne; Danielle M. Allen; Stephen J. Bridgett; Clara H. Radulescu; Michael Glenn; John-Paul Wilkins; Francesco Rubino; Behnam Firoozi Nejad; Cormac McSparron; Marc Niebel; et al. (Water Research, 2025)

A modified scoping review of interventions for global post stroke spasticity - Areerat Suputtitada; Supattana Chatromyen; Carl PC. Chen; David M. Simpson (Toxicon, 2025)

Long chain n-alkanes in lake sediment track differences in adjacent land vegetation. - Bowen Xiao; Dënë Cheecham-Uhrich; David C. Eickmeyer; Linda E. Kimpe; Vilmantas Prėskienis; E. Henriikka Kivilä; Meiling Man; Myrna J. Simpson; Irena Creed; Milla Rautio; Jules M. Blais (Organic Geochemistry, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Botulinum Neurotoxin Treatment Dynamics and Persistence Over 2 Years in Patients With Cervical Dystonia or Spasticity: A Retrospective Claims Database Analysis - David M. Simpson; Jonathan Bouchard; Simon Page; Dean Spurden; Seth Goldfarb; Atul T. Patel (Toxicon, 2024)

Improving toxicity prediction of metal-contaminated sediments by incorporating sediment properties - Yanfeng Zhang; Minwei Xie; David M. Spadaro; Stuart L. Simpson (Environmental Pollution, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Biomarkers in Ringed Seals Reveal Recent Onset of Borealization in the High- Compared to the Mid-Latitude Canadian Arctic - Camille de la Vega; Claire Mahaffey; David J. Yurkowski; Louisa Norman; Elysia Simpson; Sophie Smout; Steven H. Ferguson; Rachel M. Jeffreys (Frontiers in Marine Science, 2021)
Warming of the Arctic has resulted in environmental and ecological changes, termed borealization, leading to the northward shift of temperate species. Borealization has occurred across all trophic levels, altering the structure of the food web. The onset and rate of borealization likely varies with latitude, depending on local warming and advection of warmer water into the Arctic. In order to assess latitudinal trends in food web structure in the Arctic, we analyzed stable nitrogen isotopes of specific amino acids alongside bulk stable carbon isotopes in ringed seal muscle tissue from the Canadian Arctic Archipelago (high-Arctic) and Southern Baffin Bay (mid-Arctic) from 1990 to 2016. Our results indicate a shift in food web structure in the high-Arctic that has occurred more recently when compared with the mid-Arctic. Specifically, over the past 25 years, the trophic position of ringed seals from the mid-Arctic was largely constant, whereas the trophic position of ringed seals decreased in the high-Arctic, reaching similar values observed in the mid-Arctic in 2015–2016. This suggests a potential shortening of the food chain length in the high-Arctic, possibly driven by changes in zooplankton communities feeding complexity in association with sea ice decline. This study identifies a temporal offset in the timing of borealization in the Canadian Arctic, resulting in different response of food webs to ecological changes, depending on latitude.

Historical overview and new directions in bioarchaeological trace element analysis: a review - Rachel Simpson; David M. L. Cooper; Treena Swanston; Ian Coulthard; Tamara L. Varney (Archaeological and Anthropological Sciences, 2021)
Given their strong affinity for the skeleton, trace elements are often stored in bones and teeth long term. Diet, geography, health, disease, social status, activity, and occupation are some factors which may cause differential exposure to, and uptake of, trace elements, theoretically introducing variability in their concentrations and/or ratios in the skeleton. Trace element analysis of bioarchaeological remains has the potential, therefore, to provide rich insights into past human lifeways. This review provides a historical overview of bioarchaeological trace element analysis and comments on the current state of the discipline by highlighting approaches with growing momentum. Popularity for the discipline surged following preliminary studies in the 1960s to 1970s that demonstrated the utility of strontium (Sr) as a dietary indicator. During the 1980s, Sr/Ca ratio and multi-element studies were commonplace in bioarchaeology, linking trace elements with dietary phenomena. Interest in using trace elements for bioarchaeological inferences waned following a period of critiques in the late 1980s to 1990s that argued the discipline failed to account for diagenesis, simplified complex element uptake and regulation processes, and used several unsuitable elements for palaeodietary reconstruction (e.g. those under homeostatic regulation, those without a strong affinity for the skeleton). In the twenty-first century, trace element analyses have been primarily restricted to Sr and lead (Pb) isotope analysis and the study of toxic trace elements, though small pockets of bioarchaeology have continued to analyse multiple elements. Techniques such as micro-sampling, element mapping, and non-traditional stable isotope analysis have provided novel insights which hold the promise of helping to overcome limitations faced by the discipline.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Design of a Drug-Eluting Subcutaneous Implant of the Antiretroviral Tenofovir Alafenamide Fumarate - Solange M Simpson; Lakmini Widanapathirana; Jonathan T. Su; Samuel Sung; David Watrous; Jiang Qiu; Elizabeth Pearson; Alex Evanoff; Dipu Karunakaran; Jorge E. Chacon; Patrick F. Kiser (Pharmaceutical Research, 2020)
Purpose Sexual transmission of HIV has been clinically proven to be preventable with a once-daily oral tablet; however, missed doses dramatically increase the risk of HIV infection. Long-acting subcutaneous implants do not allow the user to miss a dose. A desirable long-acting drug-eluting implant can deliver a constant amount of drug, adjust the delivered dose, and be readily manufactured. We present a long-acting, subcutaneous implant design composed of tenofovir alafenamide hemifumarate (TAF) pellets loaded in a sealed polyether urethane tube for the prevention of HIV transmission. Methods Implants were prepared with pressed drug pellets and extruded polyurethane tubing. In vitro release rate of implants using different pellet formulations, rate-controlling membranes, and geometries were measured. Results Tenofovir alafenamide release appeared to be governed by a pseudo-steady state and followed a mass transport model of release from a cylindrical drug reservoir. Implant seal integrity was tested and confirmed using mechanical testing. The inclusion of sodium chloride in the pellet increased the release rate and reduced initial lag. The release was sustained for 100 days. Conclusions The release rate of tenofovir alafenamide mechanistically varied with geometry and rate controlling membrane composition. The polyether urethane implant presented herein is modular and tunable to adjust the release rate and duration of the TAF release.

Impacts of tropospheric ozone and climate change on Mexico wheat production - Jose Rafael Guarin; Lisa Emberson; David Simpson; Ixchel M. Hernandez-Ochoa; Diane Rowland; Senthold Asseng (Climatic Change, 2019)

Identification of powdery mildew resistance QTL in strawberry (Fragaria × ananassa) - Helen M. Cockerton; Robert J. Vickerstaff; Amanda Karlström; Fiona Wilson; Maria Sobczyk; Joe Q. He; Daniel J. Sargent; Andy J. Passey; Kirsty J. McLeary; Katalin Pakozdi; Nicola Harrison; Maria Lumbreras-Martinez; et al. (Theoretical and Applied Genetics, 2018)

Predictive control of intersegmental tarsal movements in an insect - Alicia Costalago-Meruelo; David M. Simpson; Sandor M. Veres; Philip L. Newland (Journal of Computational Neuroscience, 2017)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

Enigmatic spheres from the Upper Triassic Lockatong Formation, Newark Basin of eastern Pennsylvania: evidence for microbial activity in marginal-lacustrine strandline deposits - Edward L. Simpson; David L. Fillmore; Michael J. Szajna; Emily Bogner; Margariete G. Malenda; Kelsey M. Livingston; Brian Hartline (Palaeobiodiversity and Palaeoenvironments, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Detecting Extinction Risk from Climate Change by IUCN Red List Criteria - DAVID A. KEITH; MICHAEL MAHONY; HARRY HINES; JANE ELITH; TRACEY J. REGAN; JOHN B. BAUMGARTNER; DAVID HUNTER; GEOFFREY W. HEARD; NICOLA J. MITCHELL; KIRSTEN M. PARRIS; TRENT PENMAN; BEN SCHEELE; et al. (Conservation Biology, 2014)
Anthropogenic climate change is a key threat to global biodiversity. To inform strategic actions aimed at conserving biodiversity as climate changes, conservation planners need early warning of the risks faced by different species. The IUCN Red List criteria for threatened species are widely acknowledged as useful risk assessment tools for informing conservation under constraints imposed by limited data. However, doubts have been expressed about the ability of the criteria to detect risks imposed by potentially slow‐acting threats such as climate change, particularly because criteria addressing rates of population decline are assessed over time scales as short as 10 years. We used spatially explicit stochastic population models and dynamic species distribution models projected to future climates to determine how long before extinction a species would become eligible for listing as threatened based on the IUCN Red List criteria. We focused on a short‐lived frog species (Assa darlingtoni) chosen specifically to represent potential weaknesses in the criteria to allow detailed consideration of the analytical issues and to develop an approach for wider application. The criteria were more sensitive to climate change than previously anticipated; lead times between initial listing in a threatened category and predicted extinction varied from 40 to 80 years, depending on data availability. We attributed this sensitivity primarily to the ensemble properties of the criteria that assess contrasting symptoms of extinction risk. Nevertheless, we recommend the robustness of the criteria warrants further investigation across species with contrasting life histories and patterns of decline. The adequacy of these lead times for early warning depends on practicalities of environmental policy and management, bureaucratic or political inertia, and the anticipated species response times to management actions. Detección del Riesgo de Extinción a partir del Cambio Climático por medio del Criterio de la Lista Roja de la UICNKeith et al.

Latent cytomegalovirus infection and innate immune function following a 75 km cycling time trial - Emily C. P. LaVoy; David C. Nieman; Dru A. Henson; R. Andrew Shanely; Amy M. Knab; Lynn Cialdella-Kam; Richard J. Simpson (European Journal of Applied Physiology, 2013)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Erratum to: Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Arthropod food webs become increasingly lipid‐limited at higher trophic levels - Shawn M. Wilder; Michael Norris; Raymond W. Lee; David Raubenheimer; Stephen J. Simpson (Ecology Letters, 2013)
Understanding why food chains are relatively short in length has been an area of research and debate for decades. We tested if progressive changes in the nutritional content of arthropods with trophic position limit the availability of a key nutrient, lipid, for carnivores. Arthropods at higher trophic levels had progressively less lipid and more protein in their bodies compared with arthropods at lower trophic levels. The nutrients present in arthropod bodies were directly related to the nutrients that predators extracted when feeding on those arthropods. As a consequence, nutrient assimilation shifted from lipid‐biased to protein‐biased as arthropods ascended trophic levels from herbivores to secondary carnivores. Successive changes in the nutritional consequences of predation may ultimately set an upper limit on the number of trophic levels in arthropod communities. Further work is needed to examine the influence of lipid and other nutrients on food web traits in a range of ecosystems.

Adaptive feedback analysis and control of programmable stimuli for assessment of cerebrovascular function - Lingke Fan; Glen Bush; Emmanuel Katsogridakis; David M. Simpson; Robert Allen; John Potter; Anthony A. Birch; Ronney B. Panerai (Medical & Biological Engineering & Computing, 2013)

Autonomic dysfunction is common in HIV and associated with distal symmetric polyneuropathy - Jessica Robinson-Papp; Sandeep Sharma; David M. Simpson; Susan Morgello (Journal of NeuroVirology, 2013)

A system identification analysis of neural adaptation dynamics and nonlinear responses in the local reflex control of locust hind limbs - Oliver P. Dewhirst; Natalia Angarita-Jaimes; David M. Simpson; Robert Allen; Philip L. Newland (Journal of Computational Neuroscience, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Neuromuscular complications in HIV: effects of aging - Jessica Robinson-Papp; Ik Lin Tan; David M. Simpson (Journal of NeuroVirology, 2012)

The Bulbostylis capillaris complex (Cyperaceae) in southern South America - M. Gabriela López; David A. Simpson (Kew Bulletin, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Development of “universal” gene-specific markers from Malus spp. cDNA sequences, their mapping and use in synteny studies within Rosaceae - Daniel J. Sargent; Annalisa Marchese; David W. Simpson; Werner Howad; Felicidad Fernández-Fernández; Amparo Monfort; Pere Arús; Kate M. Evans; Kenneth R. Tobutt (Tree Genetics & Genomes, 2009)

Large-scale vulnerability assessments for natural hazards - David M. Simpson; R. Josh Human (Natural Hazards, 2008)

Murine model of BCG lung infection: Dynamics of lymphocyte subpopulations in lung interstitium and tracheal lymph nodes - Rajiv K. Saxena; David Weissman; Janet Simpson; Daniel M. Lewis (Journal of Biosciences, 2002)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

A Parametric Approach to Measuring Cerebral Blood Flow Autoregulation from Spontaneous Variations in Blood Pressure - David M. Simpson; Ronney B. Panerai; David H. Evans; A. Ross Naylor (Annals of Biomedical Engineering, 2001)

Objective Response Detection in an Electroencephalogram During Somatosensory Stimulation - David M. Simpson; Carlos J. Tierra-Criollo; Renato T. Leite; Eduardo J. B. Zayen; Antonio F. C. Infantosi (Annals of Biomedical Engineering, 2000)

The ferric-reducing activity of duodenal brush-border membrane vesicles is associated with a b-type haem - David J. Pountney; Kishor B. Raja; Robert J. Simpson<; John M. Wrigglesworth (BioMetals, 1999)

An assessment of suprageneric phylogeny inCyperaceae usingrbcL DNA sequences - Abraham M. Muasya; David A. Simpson; Mark W. Chase; Alastair Culham (Plant Systematics and Evolution, 1998)

An expanded collection of mouse Y Chromosome RDA clones - David E. Bergstrom; Hailing Yan; Manjula M. Sonti; Sandya Narayanswami; Janet K. Bayleran; Elizabeth M. Simpson (Mammalian Genome, 1997)